2011
DOI: 10.1111/j.1600-0854.2011.01158.x
|View full text |Cite
|
Sign up to set email alerts
|

Ezrin Promotes Actin Assembly at the Phagosome Membrane and Regulates Phago‐Lysosomal Fusion

Abstract: Phagosome maturation is defined as the process by which phagosomes fuse sequentially with endosomes and lysosomes to acquire an acidic pH and hydrolases that degrade ingested particles. While the essential role of actin cytoskeleton remodeling during particle internalization is well established, its role during the later stages of phagosome maturation remains largely unknown. We have previously shown that purified mature phagosomes assemble F-actin at their membrane, and that the ezrin-radixin-moesin (ERM) pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
65
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 73 publications
(97 reference statements)
1
65
0
1
Order By: Relevance
“…CASP4 facilitates cell migration by directly interacting with the actin interacting protein WDR1/AIP1, thereby allowing CFL1-dependent actin depolymerization in the context of chemotaxis [36]. During phagocytosis, F-actin assembly around phagosomes is crucial to guarantee efficient phagosome-lysosome fusion [60]. However, the role of CASP4-actin interaction in intracellular autophagosome trafficking is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…CASP4 facilitates cell migration by directly interacting with the actin interacting protein WDR1/AIP1, thereby allowing CFL1-dependent actin depolymerization in the context of chemotaxis [36]. During phagocytosis, F-actin assembly around phagosomes is crucial to guarantee efficient phagosome-lysosome fusion [60]. However, the role of CASP4-actin interaction in intracellular autophagosome trafficking is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that CD44 and Ezrin interact with N-WASP and promote the actin assembly via the N-WASP-Arp2/3 machinery. 30,49 Altogether, the role of CD44 both in the Wnt-independent LRP6 membrane targeting and in the Wnt-dependent LRP6 phosphorylation appear to be linked to the ability of CD44 to bind ERMs. Functions of ERMs that might explain their role in these two processes have been described.…”
Section: Discussionmentioning
confidence: 99%
“…Ezrin is an important member of the ERM family. This protein specifically binds to actin and serves as a crosslinker between the plasma membrane and the cytoskeleton [28,29]. The Ezrin (NM-003379) gene is on chromosome 6q25.2-q26 and encodes 587 amino acids [30].…”
Section: Discussionmentioning
confidence: 99%